Education as a Science and Its Relevance in the Digital Era - Amanda, Restu Rizki; Supriadi, Udin; Budiyanti, Nurti; Anugrah, Eri (MO.RI Publishing, 2025)
Although education has long been recognized as a science, the advent of the digital era has introduced new challenges regarding its relevance and effectiveness in preparing learners to meet the ever-changing demands of the workforce. Many educational institutions have not yet fully integrated digital technology optimally into the learning process, resulting in a gap between educational theory and its application in a digital context. This study aims to explore the extent to which education as a science can adapt to the developments of the digital era and how the education system can respond to the growing need for digital skills among learners. This research utilizes data sources based on literature from previous relevant studies. The article employs a qualitative approach with a literature review method to analyze the research themes. The process begins with the identification of relevant topics, followed by the collection of various literature sources. The researcher then analyzes the data to identify significant patterns and themes. The analysis results are synthesized by integrating findings from various sources, yielding a comprehensive understanding. This study demonstrates that education as a science has significant potential to adapt to the digital era. Therefore, the current education system needs to innovate and transform to meet the digital skill requirements of learners. This research implies the necessity for educational responsiveness, emphasizing the need for collaboration between curriculum developers and education practitioners to ensure that education not only keeps pace with technological advancements but also provides relevant and adaptive skills.